2017
DOI: 10.15761/ahdvs.1000102
|View full text |Cite
|
Sign up to set email alerts
|

Mycoplasmology: the big issues

Abstract: Important diseases like contagious bovine and caprine pleuropneumonia, avian mycoplasmosis, atypical pneumonia and contagious agalactia are caused by small degenerate wall-less organisms called mycoplasmas which evolved from gram positive bacteria about 2.5 billion years ago. The smallest of them are close to the theoretical limit for free-living existence containing less than 500 genes. However, they have acquired sophisticated means to survive both in the environment and in the host. Recent discoveries of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…Considering the divergent opinions about the role of the humoral response in preventing M. bovis infections it is suggested that the cellular immunity is likely to be more effective in eliminating M. bovis from the host than the humoral response (Nicholas et al, 2017). In this study all of the tested saponin-based adjuvants appeared to enhance the cell-mediated immune response but this depended on the adjuvant formulation.…”
mentioning
confidence: 71%
See 1 more Smart Citation
“…Considering the divergent opinions about the role of the humoral response in preventing M. bovis infections it is suggested that the cellular immunity is likely to be more effective in eliminating M. bovis from the host than the humoral response (Nicholas et al, 2017). In this study all of the tested saponin-based adjuvants appeared to enhance the cell-mediated immune response but this depended on the adjuvant formulation.…”
mentioning
confidence: 71%
“…Previously some vaccine studies have shown a stimulatory effect on humoral immunity but this was often not correlated with the prevention of M. bovis infection, disease, or colonisation of the upper and lower respiratory tract (Maunsell et al, 2009;Soehnlen et al, 2011). Considering the divergent reports it has been speculated that the cell-mediated immunity is necessary to destroy infected cells, and it is likely to be more effective in the elimination of M. bovis from the host than the humoral response (Nicholas et al, 2017). Information on the course of cellular immune response to M. bovis in young calves is limited.…”
mentioning
confidence: 99%
“…In fact, an increasing number of mycoplasmas have been shown to enter non-phagocytic host cells [ 28 , 48 51 ]. The intracellular phase provides a protective niche for pathogens, in order to escape the immune defense and antimicrobial drugs [ 52 ]. Worthy of interest, we herein first demonstrated that Mmm is also able to penetrate inside non-phagocytic host cells.…”
Section: Discussionmentioning
confidence: 99%
“…Although a number of mycoplasma diseases have a huge socio-economic significance, proper control strategies are missing, mainly due to lack of knowledge about their pathogenicity mechanisms. They lack typical pathogenicity factors found in other bacteria, and although genomes of many important mycoplasma pathogens have been sequenced, questions pertaining to their virulence and survival remain [ 1 3 ]. Having evolved 2.5 billion years ago from a Gram-positive ancestor, mycoplasma evolution was marked by severe genomic reduction, so that contemporary mycoplasmas have lost several metabolic pathways in addition to the genes dedicated to cell wall synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…agalactiae serves as an excellent model for studying mycoplasma pathogenesis because, unlike many other mycoplasma pathogens, (i) it grows well in the lab, (ii) the pathology associated with disease has been well-documented, (iii) many molecular tools, genomic and proteomic data are available, (iv) different sheep infection models are well-established, and most importantly, (v) it is phylogenetically very close to M . bovis [ 15 ], a worldwide serious pathogen that causes huge economic losses and induces similar clinical signs of mastitis, arthritis and pneumoniae in cattle [ 3 , 16 ]. Until 1976, M .…”
Section: Introductionmentioning
confidence: 99%